Life in five senses : [large type] how exploring the senses got me out of my head and into the world - Rubin, Gretchen (Random House Large Print, 2023)
Drawing on cutting-edge science, philosophy, literature and her own efforts to practice what she learns, the #1 New York Times best-selling author of The Happiness Project offers profound insights and practical suggestions for heightening our senses and using our powers of perception to live richer lives.